Ostensywne vs. stylistyczne funkcje terminów koloru jako centralna dychotomia lingwistyki barwy - Kulpina, Walentina G. (Stylistyka, 2021)
The article deals with the terms of colours as a very important component of language picture of the world. The paper focuses upon the specific features of colour terms on the basis of comparative study of chromatic lexemes.